2020
DOI: 10.1007/s00025-020-01273-6
|View full text |Cite
|
Sign up to set email alerts
|

Steiner Loops of Affine Type

Abstract: Steiner loops of affine type are associated to arbitrary Steiner triple systems. They behave to elementary abelian 3-groups as arbitrary Steiner Triple Systems behave to affine geometries over $${\mathrm {GF}}(3)$$ GF ( 3 ) . We investigate algebraic and geometric properties of these loops often in connection to configurations. Steiner loops of affine type, as extensions of normal subloops by factor loops, are studied. We prove that the multiplication group of every Steiner loop of affine type with n element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Moreover, it is shown that symmetric and affine resolvable 2-designs are additive and that, for these designs, and for a suitable choice of G, the blocks are exactly the (unordered) k-tuples of elements in P which sum up to zero, so that the automorphism group of D coincides with the stabilizer of P in the automorphism group of G. On the contrary, it is shown that the only additive Steiner triple systems are the point-line designs of AG(d, 3) and PG(d, 2) (cf. also [11] and [12]).…”
Section: Additive Designsmentioning
confidence: 87%
“…Moreover, it is shown that symmetric and affine resolvable 2-designs are additive and that, for these designs, and for a suitable choice of G, the blocks are exactly the (unordered) k-tuples of elements in P which sum up to zero, so that the automorphism group of D coincides with the stabilizer of P in the automorphism group of G. On the contrary, it is shown that the only additive Steiner triple systems are the point-line designs of AG(d, 3) and PG(d, 2) (cf. also [11] and [12]).…”
Section: Additive Designsmentioning
confidence: 87%
“…It is worth mentioning that algebraic representations of the STS(13)s were recently given in [31] and in [12,Proposition 4]. In the former case, an incidence structure isomorphic to a Steiner triple system of order 13 is constructed by defining a set B of twenty-six vectors in the 13-dimensional vector space V over the finite field F 5 , with the property that there exist precisely thirteen 6-subsets of B whose elements sum up to zero in V, whereas in the latter case the STS(13)s are described as sections of A(13)/A (12) in the alternating group A(13).…”
Section: The Two Steiner Triple Systems Of Order 13mentioning
confidence: 99%